Knowledge, attitudes, and practices regarding lumbar disc herniation among diagnosed patients - Xu, Ruijun; Ning, Mingliang; Yu, Ronghua; Yu, Mingchen; Yu, Jiangming; Chen, Haojie (Frontiers in Public Health, 2025)
IntroductionThis study aimed to investigate the knowledge, attitudes, and practices (KAP) of patients with lumbar disc herniation (LDH) regarding their condition.MethodsA cross-sectional study was conducted between June and September 2024 at Tongren Hospital in Shanghai and the Seventh People’s Hospital of Changzhou, targeting patients diagnosed with LDH. Demographic information and KAP scores were collected and evaluated through a structured questionnaire. The Oswestry Disability Index (ODI) was used to assess the level of disability experienced by patients in daily activities.ResultsA total of 395 valid questionnaires were collected, yielding an effective rate of 84.40%. Of the respondents, 205 (51.90%) were female, 201 (50.89%) had undergone surgical treatment. The mean ± SD scores for knowledge, attitude, practice, and ODI were 14.91 ± 5.07 (possible range: 0–22), 39.26 ± 3.78 (possible range: 10–50), 39.48 ± 6.70 (possible range: 11–55), and 12.92 ± 9.60 (possible range: 0–50), respectively. The Structural Equation Model indicated that knowledge had a direct effect on both attitude (β = 0.458, p = 0.006) and practice (β = 0.214, p = 0.002), while attitude directly affected practice (β = 0.323, p = 0.008). Knowledge also indirectly influenced practice via attitude (β = 0.148, p = 0.006).ConclusionPatients with LDH demonstrated inadequate knowledge but generally positive attitudes and proactive practices regarding their condition, along with a moderate level of disability related to low back pain. Improving patient education, particularly focusing on enhancing knowledge, may foster more positive attitudes and better self-management practices, potentially reducing disability.